Counseling as a Method of Psychological Reconciliation for Victims of Dating Violence - Inosensius Tomi Kristoper; Sutarto Wijono; Jacob Daan Enge (Buletin Psikologi, 2019)
Dating violence (DV) has psychological impacts on the victims such as depression, trauma, anxiety, decreased self-esteem and feeling of resentment. This article aims to rediscuss the process of reconciliation and its relationship to DV victims’ inner peace. The process of psychological reconciliation would help to set the victims free from the shackle of previous abusive dating relationship. Reconciliation is defined as being able to cultivate peace within oneself. Because the victims’ problem lied in the memory of abusive experiences conducted by the violent doer, one of the proposed effective techniques that can be used in psychological reconciliation is counseling for DV victims.